A microfluidic technique for the continuous synthesis of monodisperse silica supraparticles - Toshimitsu Kanai; Tomoyuki Fujisaki; Yuka Yokoyama (Journal of Asian Ceramic Societies)
Supraparticles, which comprise assemblies of primary micro/nanoparticles, have attracted significant attention in various fields, including catalysis, biotechnology, energy production, and photonics. This study reports the continuous synthesis of monodisperse silica supraparticles by a two-stage microfluidic technique. First, the liquid materials (sodium silicate solution and silicone oil with a surfactant) are injected into a flow-focusing microfluidic device to generate monodisperse droplets of the sodium silicate solution in the oil phase. The droplet-containing oil phase is then transferred to a two-phase parallel-flow microfluidic device along with the simultaneous injection of ethanol. During the parallel flow of the oil phase and ethanol, ethanol diffuses to the sodium silicate solution droplets, wherein the dissolved sodium silicate undergoes a dehydration–condensation reaction with ethanol to generate monodisperse silica supraparticles. The developed method facilitates the continuous production of monodisperse silica supraparticles, which could expedite industrial and academic research on such systems.